The Roadmap to a Low-Carbon Urban Water Utility An international guide to the WaCCliM approach - Ballard, Simone; Porro, Jose; Trommsdorff, Corinne (IWA Publishing, 2018)
The transition to low-carbon urban water utilities is an innovative idea, only embraced by a few forward thinking utilities currently. This roadmap is directed at urban water utility managers in charge of planning future actions, as well as at the stakeholders who will support the utility action plans. Because only a few "early adopters" utilities have embarked on the Low-Carbon transition, this roadmap intends to support other utilities understand and champion the need for contribution to a carbon neutral future and well as to guide them through a process of change. This roadmap is potentially applicable to all utilities worldwide, but was specifically written for utilities in emerging economies where service performance and data management challenges are often prominent in driving future planning.